EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBANTUAN MEDIA SEEDS DALAM PEMBELAJARAN MATEMATIKA PADA PESERTA DIDIK KELAS I UPT SPF SD INPRES BONTOMANAI - Dwi Anriyani; H. Baharullah; Ma’rup (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The main problem in this research is the low interest of students in learning mathematics, especially in addition material. This research aims to determine the effectiveness of the TGT type cooperative learning model assisted by seeds media in mathematics learning on the learning outcomes of class I students at UPT SPF SD Inpres Bontomanai. The population in this study were all class I students at UPT SPF SD Inpres Bontomanai with a total of 23 students. The sample was taken using a saturated sampling technique, the number of samples was all class I students of UPT SPF SD Inpres Bontomanai. The instruments used are pretest, posttest and questionnaire sheets. The results of this research show that the average posttest score for students' mathematics learning outcomes after implementing the use of the teams games tournament type cooperative learning model assisted by seeds media was 84.78. From these results, it was found that 22 students obtained a score of 95.6% or in the complete category. Based on the results of the analysis of student activity data, the score was 86.91, which indicates a good category, and the results of the analysis of student response data obtained an average score of 87.82. So it can be concluded that the application of the teams games tournament type cooperative learning model assisted by seed media is effective on mathematics learning outcomes for class I students at UPT SPF SD Inpres Bontomanai.